2018
DOI: 10.1080/13811118.2017.1366960
|View full text |Cite
|
Sign up to set email alerts
|

The Differentiating Role of State and Trait Hopelessness in Suicidal Ideation and Suicide Attempt

Abstract: With suicide being a leading cause of death in the United States, research must aim to increase efficacious prevention methods. The purpose of the present study was to gain greater understanding of the difference between suicidal ideation and suicide attempt. Previous research emphasizes the role of hopelessness in attempts and ideation (Bagge, Lamis, Nadorff, & Osman, 2014 ). Yet while hopelessness offers predictive value to suicide attempt, it fails in discriminating between suicide attempters and suicide id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Trait hopelessness has been specifically linked to personality traits, including low Extraversion (355) and high Neuroticism (354,356). Notably, trait hopelessness has shown a stronger risk with suicidal behavior than state hopelessness (357). Our study generates the new hypothesis that chronic T. gondii infection may elevate risk of suicide via increasing propensity to trait hopelessness, a hypothesis that warrants further research.…”
Section: Relevancementioning
confidence: 67%
“…Trait hopelessness has been specifically linked to personality traits, including low Extraversion (355) and high Neuroticism (354,356). Notably, trait hopelessness has shown a stronger risk with suicidal behavior than state hopelessness (357). Our study generates the new hypothesis that chronic T. gondii infection may elevate risk of suicide via increasing propensity to trait hopelessness, a hypothesis that warrants further research.…”
Section: Relevancementioning
confidence: 67%
“…The ecological momentary assessment showed that, even though hopelessness fluctuates over time, it has a significant association with both passive and active suicidal ideation [ 26 ]. Trait hopelessness was shown to have a stronger association with suicidal ideation than hopelessness influenced by depression symptoms [ 27 ]. This observation parallels the findings of our study in which hopelessness at baseline, and not the severity of depression, was the strongest predictor of membership to the unfavorable suicidal ideation trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents' level of suicidality over the past 12 months was measured using the suicidal thoughts and acts subscale from the Psychiatric Symptom Frequency Scale (PSFS) [29], which was originally developed in the United Kingdom and has been used in both Australia and North America [30][31][32][33]. The subscale consists of 5 items concerning suicidal thoughts and acts that are each presented with dichotomous response options (yes and no).…”
Section: Stbmentioning
confidence: 99%